DNS blocking in AE: bbc.com, facebook.com, google.com, instagram.com, medium.com +13 more (United Arab Emirates) - Voidly (2026)
CRITICAL severity censorship detected in United Arab Emirates. Confidence: 85%. Data sourced from CensoredPlanet.
Censorship Incident ID: AE-2026-0001
Keywords: censorship; AE; censorship; critical